Potential improvement in spatial accessibility of methadone treatment with integration into other outpatient substance use disorder treatment programs, New York City, 2024. - Marcus A Bachhuber; Chinazo O Cunningham; Ashly E Jordan (PLoS ONE)
Background Methadone is an effective treatment for opioid use disorder; however, its provision in the US is limited to federally-regulated opioid treatment programs (OTP). Expansion of methadone treatment into non-OTP substance use disorder (SUD) treatment programs ('expanded methadone treatment access') is a promising intervention to increase access. Methods We performed a cross-sectional geospatial analysis of public transit times to OTPs, expanded methadone treatment access, and other healthcare facilities as of March, 2024 in New York City (NYC). We estimated one-way public transit travel time and compared travel times using population weighted paired t-tests. Results For OTPs, 38.2% (95% CI: 38.0, 38.4) of the NYC population was within 15 minutes and 79.7% (95% CI: 79.5, 79.9) was within 30 minutes. For expanded methadone treatment access, 72.1% (95% CI: 71.9, 72.2) of the NYC population was within 15 minutes and 97.5% (95% CI: 97.5, 97.6) was within 30 minutes. The mean travel time was 20.4 minutes (SD: 10.9) for OTPs and 12.1 minutes (SD: 7.1) for expanded methadone treatment access (difference: -8.3 minutes [95% CI: -8.5, -8.1]; P < 0.001). The mean travel time for expanded methadone treatment access was slightly longer than the mean travel time for dialysis facilities (difference: 0.22 minutes [95% CI: 0.06, 0.39]; P = 0.009]), not significantly different than Federally Qualified Health Centers (difference: -0.06 minutes [95% CI: -0.22, 0.11]; P = 0.51), and significantly shorter than the mean travel time to ambulatory surgical centers (difference: -6.3 [95% CI: -6.5, -6.0]; P < 0.001) and hospitals (difference: -8.1 [95% CI: -8.3, -7.9]; P < 0.001). Conclusion Efforts to increase access to methadone treatment in the US should promote expansion to additional non-OTP outpatient SUD treatment programs. Such integration is anticipated to increase spatial accessibility of methadone treatment substantially, greatly enhancing the potential for patient access.